The Influence Of Organizational Culture And Leadership Style On Employee Performance - Aldi Alfathur Rachman; Muhammad Julda Al Hafiz; Puput Vernanda; Indah Rizki Maulia (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This article is a review of the relevant literature, and its purpose is to formulate research hypotheses concerning the interaction of variables that will be utilized in subsequent research, particularly in the field of Human Resource Management. For the purpose of writing the article on the literature review, the library research method was utilized, and online sources such as Google Scholar, Mendeley, and other academic online platforms were utilized. This literature review article's findings are comprised of three primary aspects, which are as follows: First, the influence of the organization's culture; second, the leadership style; and third, the performance of the employees. In addition to the exogenous variables that have been mentioned above, there are a great number of other factors that have an effect on the endogenous variable of motivation and performance. These factors include organizational culture, leadership style, and employee performance.